2013
DOI: 10.1136/gutjnl-2013-305088
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor agonists attenuate colonic epithelial secretory function and prevent experimental diarrhoea in vivo

Abstract: These data reveal a novel antisecretory role for the FXR in colonic epithelial cells and suggest that FXR agonists have excellent potential for development as a new class of antidiarrheal drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 43 publications
(44 reference statements)
1
49
2
2
Order By: Relevance
“…Depending on their concentrations within the colonic lumen, BA can have, via FXR signaling, not only a prosecretory but also an anitsecretory effect (Keating et al, 2009). Intraluminal BA in moderate quantities can prevent fluid accumulation in the intestine by inhibition of the Na + channel and K + -ATPase expression (Mroz et al, 2013); expression of both transporters was described as decreased in UC colitis (Greig et al, 2004;Sullivan et al, 2009). Our studies in adolescent IBD reveal low ileal FGF-19 levels in CD and UC.…”
Section: Discussionmentioning
confidence: 94%
“…Depending on their concentrations within the colonic lumen, BA can have, via FXR signaling, not only a prosecretory but also an anitsecretory effect (Keating et al, 2009). Intraluminal BA in moderate quantities can prevent fluid accumulation in the intestine by inhibition of the Na + channel and K + -ATPase expression (Mroz et al, 2013); expression of both transporters was described as decreased in UC colitis (Greig et al, 2004;Sullivan et al, 2009). Our studies in adolescent IBD reveal low ileal FGF-19 levels in CD and UC.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequent studies have shown that the antisecretory actions of DCA and CDCA are mimicked by the FXR agonists GW4064 and OCA 54 . Thus, activation of the FXR with either of these agonists led to a dose-dependent inhibition of subsequent Ca 2+ and adenosine 3′,5′-cyclic monophosphate–dependent Cl - secretory responses, both in cell culture and in ex vivo colonic tissues from mice.…”
Section: Bile Acids and Colonic Fluid And Electrolyte Transportmentioning
confidence: 99%
“…Bile acid diarrhea results from excessive bile acid synthesis in the liver, bile acid malabsorption and a reduction in engagement of the FGF-19-mediated feedback loop that normally controls bile acid synthesis [18] . In contrast, in healthy subjects, bile acids engage the FXR and TGR5 receptors to control electrolyte homeostasis and prevent excessive water loss through diarrhea [18,47] .…”
Section: Irritable Bowel Syndrome and Diarrheamentioning
confidence: 99%